2004
DOI: 10.1097/01.sla.0000141194.27992.32
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Nonoperative Treatment for Stage 0 Distal Rectal Cancer Following Chemoradiation Therapy

Abstract: Stage 0 rectal cancer disease is associated with excellent long-term results irrespective of treatment strategy. Surgical resection may not lead to improved outcome in this situation and may be associated with high rates of temporary or definitive stoma construction and unnecessary morbidity and mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
1,140
5
62

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,600 publications
(1,221 citation statements)
references
References 41 publications
14
1,140
5
62
Order By: Relevance
“…Angelita Habr-Gama, a colorectal surgeon from Brazil, pioneered the wait-and-see or watch-and-wait approach for rectal cancer patients [29][30][31]. This policy, which is also called non-operative management or no immediate surgery, is indicated for selected patients who show a clinical complete response (cCR) post-nCRT.…”
Section: No Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Angelita Habr-Gama, a colorectal surgeon from Brazil, pioneered the wait-and-see or watch-and-wait approach for rectal cancer patients [29][30][31]. This policy, which is also called non-operative management or no immediate surgery, is indicated for selected patients who show a clinical complete response (cCR) post-nCRT.…”
Section: No Surgerymentioning
confidence: 99%
“…Habr-Gama et al conducted a series of studies in which patients with principally T3 or N1 mid/low rectal tumors, who exhibited post-nCRT cCR, underwent close surveillance only [30][31][32][33][34]. The latest report found that this non-operative approach afforded a 5-year rate of local recurrence "not amenable to salvage" as low as 6% [33,34].…”
Section: No Surgerymentioning
confidence: 99%
“…The paradigm of non-operative management of rectal cancer was pioneered in Brazil (91). Cultural differences may trigger and propel surgical development in one part of the world that would probably not have evolved in other places.…”
Section: Study IVmentioning
confidence: 99%
“…The described concept has been taken one step further by Habr-Gama (Habr-Gama et al, 2004) who did not find a need for subsequent surgery in patients with clinically complete responses. In her retrospective, long-term, follow-up study which so far has remained unique, she reports a LR rate of only 3% in 100 patients.…”
Section: Tem In Rectal Cancer After Chemoradiationmentioning
confidence: 99%